Filling or Abusing the Institutional Void? Ownership and Management Control of Public Family Businesses in an Emerging Market - Luo, Xiaowei Rose; Chung, Chi-Nien (Organization Science, 2013)
Despite increased attention given to family firms in the theory of organization and management, the value of family governance in emerging markets is not clearly understood. We draw insights from agency and institutional economics perspectives to address the debate on whether family governance fills or abuses the void left by weaker market and legal institutions. We propose a dual focus on the pattern of family control and weak institutions to reconcile these opposed assessments. We analyze how various combinations of family control over ownership, strategy, and operations yield different benefits and costs for the operational performance of firms in the absence of strong market and legal institutions. The uneven development of market institutions across industries and the impact of independent directors reinforce the importance of separating different patterns of family control. We find support for our hypotheses when tested on a data set consisting of all publicly listed firms in Taiwan between 1996 and 2005. Our study contributes to a deeper understanding of family businesses in emerging markets, highlights the importance of weak institutions in shaping relative agency costs, and illuminates the differential effects of independent directors.